ADAMTS 1, 4, 12, and 13 levels in maternal blood, cord blood, and placenta in preeclampsia. (2nd January 2018) - Namlı Kalem, Müberra; Kalem, Ziya; Yüce, Tuncay; Soylemez, Feride
ABSTRACT: The aim of this study is to compare ADAMTS (A Disintegrin and Metalloprotease Domains with Thrombospondins motifs) 1, 4, 12, and 13 levels in maternal and cord blood and placental tissue between preeclampsia and uncomplicated pregnancies. The enzyme-linked immunosorbent assay (ELISA) results showed that ADAMTS 1, 4, 12, and 13 levels in the maternal and cord blood were lower in the preeclampsia group than in the control group. Based on the immunohistochemistry (IHC) results, ADAMTS 1, 4, and 12 levels in placental tissues were higher in the preeclampsia group. According to the polymerase chain reaction (PCR) results, ADAMTS 1, 4, and 12 were higher, whereas ADAMTS 13 was lower in the preeclampsia group than in the control group.